Afrikaans in Film: From Apartheid Propaganda to Cultural Preservation - Anna-Marie Jansen van Vuuren; André Velthuysen (Mise au Point)
This article delves into the transition of Afrikaans from a hegemonic language to a minority language post-1994. Afrikaans was one of the two official South African languages in the 20th century. Afrikaans films enjoyed privileges because the government manipulated racial and cultural identities through subsidies and audience segregation. However, in the post-apartheid era, Afrikaans filmmakers had to find new funding models, such as relying on the Afrikaans satellite channel, kykNET, to commission content for cinema distribution. The article briefly discusses the symbiosis between the Afrikaans language and its film industry and how Afrikaans film remains sustainable despite not being one of South Africa’s most spoken languages.